Creep-feeding to stimulate metabolic imprinting in nursing beef heifers: impacts on heifer growth, reproductive and physiological variables. (20th May 2015) - Reis, M. M.; Cooke, R. F.; Cappellozza, B. I.; Marques, R. S.; Guarnieri Filho, T. A.; Rodrigues, M. C.; Bradley, J. S.; Mueller, C. J.; Keisler, D. H.; Johnson, S. E.; Bohnert, D. W.
Abstract : This experiment compared growth, physiological, and reproductive responses of beef heifers with (MI) or without (CON) access to a creep-feeder, as a manner to stimulate metabolic imprinting while nursing their dams. On day 0, 60 Angus×Hereford heifers were ranked by BW and age (140±3 kg and 68±3 days), and assigned to pairs so all ranking criteria were similar between heifers within each pair. On day 1, pairs were randomly assigned to MI ( n= 15) or CON ( n =15). From day 1 to 51, MI pairs and their dams were allocated to 15 drylot pens where heifers had ad libitum access to a corn-based supplement through a creep-feeder. The CON pairs and their dams were maintained in an adjacent single drylot pen. From day 52 to 111, treatments were managed as a single group on a semiarid range pasture. On day 111, heifers were weaned and allocated to two pastures (one pasture/treatment), receiving hay and a corn-based concentrate until day 326. Heifer BW was recorded before and at the end of the creep-feeding period (day 1 to 51), and on days 112 and 326. On days 0, 51, 111, 187, 261, and 325, jugular blood was collected and real-time ultrasonography for longissimus muscle depth and backfat thickness assessment was performed. Blood was also collected every 10 days from days 113 to 323 for puberty evaluation via plasma progesterone. Liver and subcutaneous fat biopsies were performed on days 51, 111, 261 and 325. Average daily gain was greater ( P< 0.01) for MI than CON from day 1 to 51, tended ( P= 0.09) to be greater for CON than MI from day 112 to 326, while BW on day 326 was similar between treatments. On day 51, MI had greater ( P ⩽0.01) plasma IGF-I and glucose concentrations, as well as mRNA expression of hepatic pyruvate carboxylase and adipose fatty acid synthase than CON. On days 261 and 325, plasma insulin concentrations were greater ( P ⩽0.03) in CON than MI. Mean mRNA expression of hepatic IGF-I and adipose peroxisome proliferator-activated receptor gamma were greater ( P ⩽0.05) in MI than CON. No treatment effects were detected for puberty attainment rate. In conclusion, supplementing nursing heifers via creep-feeding for 50 days altered physiological and biochemical variables suggestive of a metabolic imprinting effect, but did not hasten their puberty attainment.